Transfer Pricing Based on Actual versus Standard Costs - Stephan Lengsfeld; Ulf Schiller (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
The use of information plays an important role in the choice of transfer prices (TP). We discuss the information provision of two centralized mechanisms, namely, actual-cost and standard-cost based TP. Actual cost based TP use all available cost information whereas standard cost based TP only reflect expected cost. We analyze the impact of either regime on the incentives of two divisions that make upfront investments and - later - trade an intermediate good. Actual cost based TP allow for a flexible adjustment of the trade decision to the realization of marginal costs but lead to under-investment and under-trade. Standard cost based TP provide excellent investment incentives but loose flexibility. Which of both TP regimes is superior thus depends on the amount of uncertainty, the returns on investments and the average profitability of trade
urn:nbn:de:bsz:21-opus-18420
Keywords: M40; D23; 330; Transfer Pricing; Hold Up Problem; Intrafirm Trade; Incomplete Contracts; Innerbetriebliche Leistungsverrechnung; Transferpreis; Kostenrechnung; Ökonomischer Anreiz; Investition; Aussenwirtschaft; Theorie